2012
DOI: 10.1186/1471-2431-12-105
|View full text |Cite
|
Sign up to set email alerts
|

Early cessation of breastfeeding amongst women in South Africa: an area needing urgent attention to improve child health

Abstract: BackgroundBreastfeeding is a critical component of interventions to reduce child mortality. Exclusive breastfeeding practice is extremely low in South Africa and there has been no improvement in this over the past ten years largely due to fears of HIV transmission. Early cessation of breastfeeding has been found to have negative effects on child morbidity and survival in several studies in Africa. This paper reports on determinants of early breastfeeding cessation among women in South Africa.MethodsThis is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
96
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 29 publications
10
96
2
Order By: Relevance
“…Even in the early years of the national PMTCT programme, a study done from 2002 to 2003 showed poor infant feeding practices among both women with and without HIV, with less than 10% exclusively breastfeeding at 12 weeks [7]. High rates of formula feeding were also reported among women with HIV, when free infant formula was available [810]. In a study done in Cape Town, over 90% of postpartum women with HIV reported ever using infant formula, including a large proportion of women who had also breastfed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Even in the early years of the national PMTCT programme, a study done from 2002 to 2003 showed poor infant feeding practices among both women with and without HIV, with less than 10% exclusively breastfeeding at 12 weeks [7]. High rates of formula feeding were also reported among women with HIV, when free infant formula was available [810]. In a study done in Cape Town, over 90% of postpartum women with HIV reported ever using infant formula, including a large proportion of women who had also breastfed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Infant feeding practices in South Africa are found to be substandard, whereby mixed feeding is the most common practice even before 6 months of age (Doherty et al, 2012, Siziba, Jerling, Hanekom, & Wentzel-Viljoen, 2015. The South African National Health and Nutrition Examination Survey of 2012 reported the exclusive breastfeeding rates for the first 6 months of life to be very low at 7.4% nationwide, despite the high rates (83.0%) of breastfeeding initiation (South Africa HSRC 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, exclusive breastfeeding rates, regardless of HIV status, remains low at approximately 32% 17 . Breastfeeding practices among uninfected mothers are slightly better compared to HIV-infected mothers 18,19 , but are still below ideal targets 20 .…”
Section: Introductionmentioning
confidence: 94%
“…Many studies examining barriers and facilitators of breastfeeding in LMIC, including South Africa has since been generated 19 . Pregnancy and gestational factors such as unplanned pregnancy, nulliparity, caesarean section, infant male gender and low birth weight to be negatively associated with breastfeeding behaviour 14,21,22 .…”
Section: Introductionmentioning
confidence: 99%